Evolution of antibody profiles against SARS-CoV-2 in experienced and naïve vaccinated elderly people - Sanz-Muñoz, Iván; López-Mongil, Rosa; Sánchez-Martínez, Javier; Sánchez-de Prada, Laura; González, Marta Domínguez-Gil; Pérez-SanJose, Diana; Rojo-Rello, Silvia; Hernán-García, Cristina; Fernández-Espinilla, Virginia; de Lejarazu-Leonardo, Raúl Ortiz; Castrodeza-Sanz, Javier; Eiros, José María (Frontiers in Immunology, 2023)
The third dose of the COVID-19 vaccine is especially necessary in people over 65 years of age due to their lower immune response. We designed a multicentre, prospective observational study including 98 people ≥65 years old who lived in two nursing homes in Valladolid, Spain. One of the groups had previous experience with SARS-CoV-2 (n=68;69.4%) and the other was naïve (n=30;30.6%). We evaluated the response to the three doses of the Comirnaty vaccine and the dynamics of antibodies during 5 consecutive serum samplings: 2 after the first two doses of vaccination, one three months after the first dose, another at 6 months and the last one month after the third dose. IgG antibodies against SARS-CoV-2 S1, RBD and N antigens were analysed. Both groups increased the level of Abs against S1 and RBD, but the experienced group showed a 130-fold higher humoral response due to hybrid immunisation (infection+vaccination). The response to vaccination with Comirnaty against COVID-19 was higher in those ≥65 years with previous experience than those who were naïve. However, the amount of antibodies against S1 and RBD equalised at 6 months. After the third dose, both groups raised the amount of antibodies to a similar level. The reinfections suggested by the analysis of antibodies against N were frequent in both groups. The third dose showed a clear benefit for elderly people, with the reinforcement of the antibody levels after the decline suffered after six months of the first two doses.